2021
DOI: 10.48550/arxiv.2105.12169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulating Observations of Ices in Protoplanetary Disks

Nicholas P. Ballering,
L. Ilsedore Cleeves,
Dana E. Anderson

Abstract: Ices are an important constituent of protoplanetary disks. New observational facilities, notably JWST, will greatly enhance our view of disk ices by measuring their infrared spectral features. We present a suite of models to complement these upcoming observations. Our models use a kineticsbased gas-grain chemical evolution code to simulate the distribution of ices in a disk, followed by a radiative transfer code using a subset of key ice species to simulate the observations. We present models reflecting both m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 65 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…A promising mechanism to reduce water ice at a higher disk surface is photodesorption caused by far-ultraviolet photons (Dominik et al 2005;Oka et al 2012;Furuya et al 2013;Kamp et al 2018;Ballering et al 2021). Oka et al (2012) examined the impact of photodesorption on the location of the water snowline at the disk surfaces of HD 142527, and they found that the snowline is likely located between 100 au and 300 au, which is similar to the region seen in scattered light in Honda et al (2009).…”
Section: Hd 142527mentioning
confidence: 94%
See 2 more Smart Citations
“…A promising mechanism to reduce water ice at a higher disk surface is photodesorption caused by far-ultraviolet photons (Dominik et al 2005;Oka et al 2012;Furuya et al 2013;Kamp et al 2018;Ballering et al 2021). Oka et al (2012) examined the impact of photodesorption on the location of the water snowline at the disk surfaces of HD 142527, and they found that the snowline is likely located between 100 au and 300 au, which is similar to the region seen in scattered light in Honda et al (2009).…”
Section: Hd 142527mentioning
confidence: 94%
“…For the outer disk, we consider grain models presented in Section 2.1, and these grains are assumed to be well mixed throughout the outer disk. To clarify the influence of grain size on ice features, we also assume the same ice abundance across the outer disk, although ice abundance may vary radially and vertically in more realistic disk models (Oka et al 2012;Kamp et al 2018;Tung & Hoang 2020;Ballering et al 2021). This suggests that an ice abundance inferred by our simulations may correspond to the average ice abundance along each line of sight.…”
Section: Star and Disk Modelsmentioning
confidence: 99%
See 1 more Smart Citation